Occupational Exposure and Pulmonary Function of Workers of Carpet Industries and Sawmills, Lalitpur, Nepal - Das, PKL; Nepal, GB; Upadhyay-Dhungel, K; Panta, R; Bhaila, A; Shakya, B (Asian Journal of Medical Sciences, 2013)
Background: Most workers of carpet factory and sawmills suffer from non-specific lung diseases and ventilatory disorders. There is so many such industries operative in Lalitpur district and so far not many studies have been reported on pulmonary function in these workers. Method: A brief clinical sheet regarding age, occupational particulars, smoking habits and presence or absence of major complaints was recorded for each worker. Spirometric parameters were recorded using an electronic (MEDSPIROR) spirometer. The groups consisted of control subjects not exposed to industrial dusts (n=50) for each group of workers (carpet factory, n=50 and saw mill, n=50). Result: This study indicated an overall reduction in pulmonary function parameters; in particular FVC, FEV1 and FEV1/FVC % in carpet factory workers and FEV1 and FEV1/FVC % in saw mill workers. Comparison of pulmonary function parameters between carpet factories workers and sawmill workers revealed a significant reduction in FEV1 and MVV in carpet workers. Conclusion: Exposure to cotton dust and wood dust leads to combined type of spirometric deficit revealing obstructive or restrictive lung diseases. Workers exposed to industrial dusts also suffer from various upper or lower respiratory symptoms. DOI: http://dx.doi.org/10.3126/ajms.v5i2.8951 Asian Journal of Medical Science, Volume-5(2) 2014: 54-58